A taxonomic review of the genus Euboeus Boieldieu, 1865 (Coleoptera: Tenebrionidae: Helopini) of the Caucasus, Iran and Turkmenistan - Nabozhenko, Maxim V. (Zootaxa, 2022)
A taxonomic review of the genus Euboeus from the Caucasus, Iran and Turkmenistan is given. All revised species belong to the subgenus Pelorinus Vauloger de Beaupré, 1900 and can be divided into two groups: the tenebricosus species-group and the huedepohli species-group. The first one consists of mainly forest low mountain species, while the second one includes high mountain, alpine or steppe taxa. Only one species, E. сhorasanicus (Medvedev, 1976), has mixed characters and unknown habitats. In total, 11 species of the genus are known from Iran, one species is distributed in Iran and Turkmenistan. Euboeus prometheus is hereby excluded from the fauna of Azerbaijan, the species occurs on Iranian part of Talysh Mts. Euboeus quadricollis (Ménétriés, 1832) is recorded from Iran for the first time. The following new species are described: Euboeus grimmi sp. nov. (Iran, Western Elburs), E. kasatkini sp. nov. (Iran, Central Elburs), E. krivokhatskyi sp. nov. (Iran, Western Elburs and Zagros), E. merkli sp. nov. (Iran, Central Elburs), E. arzanovi sp. nov. (Iran, Central Elburs), E. zubovi sp. nov. (Iran, Zagros, Kordestan Prov.), E. kalashiani sp. nov. (Armenia, Azerbaijan: Nakhchivan, North-Western Iran). The following new synonimies are established: Helops corrugosus Seidlitz, 1895 = Probaticus parthorum G. Medvedev, 1976, syn. nov.; Helops vicinus Allard, 1876 = Probaticus (Pelorinus) medvedevi Abdurakhmanov et Nabozhenko, 2011, syn. nov. The lectotype for Helops corrugosus is designated to fix the taxonomic status of that species. In addition, illustrated identification keys for males and females of Caucasian, Iranian and Turkmen Euboeus are provided.